Jon Sobrino’s Spirituality of Incarnation Toward Political Holiness (Hekima Review, 2009)
This article begins with a few biographical details on Jon Sobrino and moves on to an explanation of the spirituality of incarnation. According to Sobrino, spirituality means “life with spirit” and spirituality of incarnation means “vitality of faith.” In this perspective, the spirituality of martyrdom is concerned with the spirit of sacrifice and self-donation, whereas political holiness deals with “contemplation in action.” As a practical spirituality, Jon Sobrino’s spirituality of incarnation helps us to propose an African spirituality of liberation which takes into account the practical, spiritual and incultural dimensions of liberation.